2003
DOI: 10.1093/pch/8.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Where physicians look for information on drug prescribing for children

Abstract: BACKGROUND: Despite the important role of drug therapy in children, there is often a lack of readily available information regarding the indications and dosing regimens for medications in paediatrics. OBJECTIVE: To collect data on where family physicians obtain this prescribing information. METHOD: A structured questionnaire was mailed to 500 family physicians in Ontario. RESULTS: Questionnaires were returned by 261 (52%) family physicians, 217 (83%) of whom identified themselves as currently involved in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The total response rate to this survey was good (67%) and is comparable to response rates obtained for other medicines information-related studies (4,5,6,11). The response rate for nurses was slightly higher, with the highest response received from practice nurses.…”
Section: Discussionsupporting
confidence: 75%
“…The total response rate to this survey was good (67%) and is comparable to response rates obtained for other medicines information-related studies (4,5,6,11). The response rate for nurses was slightly higher, with the highest response received from practice nurses.…”
Section: Discussionsupporting
confidence: 75%
“…A study [73] found that the official information for paediatric anti-cancer drug therapies was scarce, despite the availability of clinical and pharmacological studies in the literature. The problem behind the large extent of off-label and unlicensed use is therefore also due to a lack of harmonisation between the evidence and drug licenses [26,45]. Formularies remain an important source of prescribing information for physicians because they attempt to fill this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating off‐label drug use is therefore important, but different from evaluating prescribing rationality. The problem of off‐label and unlicensed drug use exists because of different reasons: an inadequate drug evaluation and registration process, a lack of documented evidence on therapies, and a lack of harmonization between the evidence and the official information available to doctors (Summary of Product Characteristics) 27. Concerning the latter, for example, one study evaluated the licence status of anticancer drugs 20 and found that the official information for paediatric anticancer drug therapies was scarce, despite the availability of clinical and pharmacological studies in the literature.…”
Section: Discussionmentioning
confidence: 99%